Cargo Business Contribution to Logistics Services at Class I Main Airport Juwata Tarakan - Wiryamanta Sistira, Rossy; Budiarto, Anton; Iswahyudi, Prasetyo (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Shipping goods by air, goods security is actually very well maintained because security continues to use aircraft as a key factor in maintaining customer confidence in shipping goods. Therefore, cargo/goods receiving operations services through airports, including loading and unloading, transfers from aircraft to warehouses (cargo warehouses). Compiler and storage and delivery of goods to the owner, must arrive safely and everything is fine. This Study aims to describe the facts about the questions posed by the author. So that the facts and valid data facilitate the analysis of effective and efficient problem solving by the author. Items that are not neatly placed in the cage can be stepped on or subjected to shocks or friction which can result in damage. This research uses a qualitative descriptive research method, namely research that uses a case study method or approach. This research is very focused on a particular topic being studied as a case, and case data can be obtained from all parties.. In addition, the placement of scattered goods also has the potential to increase the risk of loss of cargo. can affect customer confidence so that the cargo unit should be able to maximize to complete the existing facilities at the cargo terminal of the Main Juwata Tarakan Airport Class 1. The results of this study are that air cargo has advantages compared to sea and land cargo where shipping goods using air cargo can save time and reach a wide area. Despite these advantages, there is a problem that the cargo cannot be sent because the documents listed in the SMU and the contents of the cargo are different. The need to carry out cargo handling in accordance with applicable SOPs to avoid these problems.